Methacrylate and Styrene Block Copolymer Synthesis by Cu‐Mediated Chain Extension of Acrylate Macroinitiator in a Semibatch Reactor. Issue 3 (22nd December 2021) - Cooze, Morgan J.; Deacon, Hayden M.; Phe, Katrina; Hutchinson, Robin A.
Abstract: A process for the well‐controlled growth of acrylates by Cu‐mediated polymerization has been developed, with macroinitiator synthesized continuously in a copper tubular reactor and subsequently chain‐extended in a semibatch reactor without additional copper. Extending this process to methacrylates and styrene, however, has proven difficult due to a significant reduction in reaction rate. This barrier has been overcome by chain‐extending the low molecular weight ( Mn of 760 g mol –1 ) poly(methyl acrylate) macroinitiator with methacrylates and styrene using PMDETA ( N, N, N ′, N ″, N ″‐pentamethyldiethylenetriamine) as ligand. Methyl methacrylate conversions of >80% at 70 °C and diethylene glycol methyl ether methacrylate conversions of >90% at room temperature are achieved in 4 h, with the same room temperature conditions successfully applied for controlled chain extensions with butyl methacrylate. Although styrene conversions are slightly lower (60–70%) over 4 h at 85 °C, the rates achieved are substantially higher than achieved in other studies. Hydrophobic–hydrophilic triblock structures are produced through sequential monomer feeds to the semibatch reactor, keeping total reaction time to less than 5 h. The ability to incorporate methacrylates and/or styrene into structured block polymers greatly extends the range of products that can be efficiently synthesized with low copper levels by this process. Abstract : Reaction conditions to chain‐extend poly(methyl acrylate) macroinitiator with methacrylates or styrene in a semibatch process are optimized, with the versatility of the process demonstrated by the synthesis of several block structures. High monomer conversions and low residual copper levels can be achieved in <5 h, with the efficient process aligning with the 12 Principles of Green Chemistry.